Diagnostic Problem and Management of Intestinal Tuberculosis - Ryan Ranitya; Ari Fahrial Syam; Marcellus S Kolopaking; Vera Yoewono (The Indonesian Society for Digestive Endoscopy, 2001)
Intestinal tuberculosis, without any evidence of pulmonary or tuberculous infection elsewhere in the body, is still a rare case. Sometimes it is very difficult to make an early and prompt diagnosis for this, because clinical manifestations are varied, unspecific, and mimic other diseases. Examinations, including chest x-ray, tuberculin test, acid-fast stained smear, endoscopic and histological findings may still be inconclusive. Thus, therapeutic trials of anti- tuberculous drugs are advised. We report a case of intestinal tuberculosis with a chief clinical manifestation of chronic diarrhea. There was no evidence of tuberculous infection elsewhere in the body Endoscopic appearance and histological findings were atypical and unspecific. The patient was given anti- tuberculous drugs and responded very well clinically within 2 weeks. Keywords: Intestinal tuberculosis, difficult diagnosis, management